Oncolytic virus and CAR-T cell therapy in solid tumors - Ponterio, Eleonora; Haas, Tobias Longin; De Maria, Ruggero (Frontiers in Immunology, 2024)
Adoptive immunotherapy with T cells, genetically modified to express a tumor-reactive chimeric antigen receptor (CAR), is an innovative and rapidly developing life-saving treatment for cancer patients without other therapeutic opportunities. CAR-T cell therapy has proven effective only in hematological malignancies. However, although by now only a few clinical trials had promising outcomes, we predict that CAR-T therapy will eventually become an established treatment for several solid tumors. Oncolytic viruses (OVs) can selectively replicate in and kill cancer cells without harming healthy cells. They can stimulate an immune response against the tumor, because OVs potentially stimulate adaptive immunity and innate components of the host immune system. Using CAR-T cells along with oncolytic viruses may enhance the efficacy of CAR-T cell therapy in destroying solid tumors by increasing the tumor penetrance of T cells and reducing the immune suppression by the tumor microenvironment. This review describes recent advances in the design of oncolytic viruses and CAR-T cells while providing an overview of the potential combination of oncolytic virotherapy with CAR-T cells for solid cancers. In this review, we will focus on the hostvirus interaction in the tumor microenvironment to reverse local immunosuppression and to develop CAR-T cell effector function.Cancer treatment has undergone a radical transformation thanks to groundbreaking advancements in research and drug development. While chemotherapy once stood as the primary treatment, targeting rapidly dividing cancer cells, it also affected proliferating healthy cells, such as those of the epithelial and hematopoietic compartments. However, the advent of molecular profiling and understanding of